THE INFLUENCE OF TOURIST ATTRACTION AND SERVICE QUALITY ON THE INTEREST OF VISITING TOURISTS ON TKL ECOPARK - Cahyani, Fella Ardina; Al Lukman, Lucki; Lestari, Dwi Wahyu; Janah, Ana Naimatul; Trimah, Slamet (Transpublika Publisher, 2023)
This study aims to examine the effect of tourist attraction and service quality on tourists' intention to return. The data used in this study are primary data and secondary data. Primary data was obtained based on surveys or questionnaires, observations, and interviews, while secondary data was obtained through websites, journals, books, and other documents. This study involved 69 respondents who were taken randomly at Taman Kyai Langgeng. The type of research used in this research is quantitative research which is carried out by collecting data in the form of a number format and analyzing it with multiple linear regression statistical tests. The results showed that the variable tourist attraction partially did not significantly influence the intention of visiting tourists.